Understanding Indonesia's Baby Bust: Demographic Implications of Marriage Law Reform and Islamic Legal Perspectives - Yulizain Putra; Misi Anggraini; Elfia; Zulfan (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
Indonesia has recently experienced declining marriage and fertility rates, raising concerns about an emerging baby bust phenomenon and its long-term demographic implications. This study examines the relationship between Marriage Law No. 16 of 2019, which raised the minimum marriage age to 19 years, and the decline in marriage rates from the perspective of Islamic jurisprudence. Using a qualitative juridical-empirical approach, the study analyzes classical fiqh texts, including Al-Umm, Al-Hidayah, Al-Mudawwanah, and Al-Mughni, alongside marriage statistics published by Statistics Indonesia (BPS) from 2015 to 2023. The findings indicate a significant decline in marriage registrations after the enactment of the law, particularly among young adults, potentially contributing to delayed family formation and lower fertility rates. Classical Islamic jurists generally regard marriage as a means of protecting lineage (hifz al-nasl) while recognizing public welfare (maslahah) as a basis for legal regulation. The study argues that the law supports child protection objectives but may generate unintended demographic consequences when not accompanied by adequate social and economic support. It recommends strengthening premarital education, expanding support programs for young families, and enhancing policy coordination between government institutions and religious authorities.